Development of a power factor correction boost converter in single phase rectifier using fuzzy logic - Mohamad, Salamiyah (2013)
Power factor correction (PFC) provides well-known benefits to avoid poor power factor penalty and to reduction bill utility. The voltage support release of the system capacity and reduce system losses. There are two kinds of power factor correction techniques- passive power factor correction and active power factor correction. This thesis tried to develop a boost converter with applied active power factor correction method for improve of the power factor. MATLAB software is used to design Fuzzy logic to control scheme for boost converter from single phase rectifier. The methodology integrates fuzzy logic controlling the output voltage of DC-DC converter and improves performance of the boost converter during transient operation. Instead of generating fast pulse-width-modulated (PWM) signal, the digital signal processor is required to generate a slow-varying dc signal only for determining the PWM ramp function. A model for Power Factor Correction has been developed using the MATLAB software. The simulation result shows that the power factor has been improved.